2016
DOI: 10.1007/s12098-016-2149-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intranasal Dexmedetomidine with Intranasal Clonidine as a Premedication in Surgery

Abstract: Intranasal dexmedetomidine is a better anxiolytic and sedative as compared to clonidine. Postoperative analgesic requirement was also significantly decreased after intranasal dexmedetomidine. Thus, it can be preferred as compared to clonidine for premedication in pediatric surgical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This difference in result may be due to the fact that in their study midazolam was only compared to placebo resulting in bias towards midazolam. Similarly, Sidhu GK et al, in their study found satisfactory sedation and anxiolysis in 60 % and 25.7% of the children receiving 3 μg/kg of intranasal clonidine, respectively (Sidhu, G. K. et al, 2016).…”
Section: Resultsmentioning
confidence: 74%
“…This difference in result may be due to the fact that in their study midazolam was only compared to placebo resulting in bias towards midazolam. Similarly, Sidhu GK et al, in their study found satisfactory sedation and anxiolysis in 60 % and 25.7% of the children receiving 3 μg/kg of intranasal clonidine, respectively (Sidhu, G. K. et al, 2016).…”
Section: Resultsmentioning
confidence: 74%
“…Among these, full text could not be found for one article, and after reading the remaining 71 articles, 51 articles that did not meet the inclusion criteria were excluded. Finally, 20 RCTs were included in this network metaanalysis [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The flowchart is shown in Fig.…”
Section: Systemic Retrieval Resultsmentioning
confidence: 99%
“…Oral routes have been extensively examined [ 24 ], but data on IN are scant. IN delivery is a simple, noninvasive approach with great bioavailability [ 25 ]. Drug delivery and development are the most important translational research contributions to human health and well-being [ 26 ].…”
Section: Discussionmentioning
confidence: 99%